SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS WEBSITE (NEW STUDENT REGISTRATION INFORMATION SYSTEM IS WEBSITE BASED) - Mau, Paul Wilfridus; Dopa, Pius C; Dalu, Faustina; Opat, Aloysius Y.D (Department of Information Technology, Universitas Timor, Indonesia, 2024)
A Web-Based New Student Registration Information System is a web application designed to streamline the process of registering new students at an educational institution. This research aims to enhance the efficiency and quality of new student registration services through the use of web technology. The system development method employed is the Waterfall method, which comprises analysis, design, implementation, testing, and maintenance phases. This system allows prospective students and parents/guardians to access information about educational programs, registration requirements, and complete registration forms online. Additional features include data verification, online registration fee payment, and the printing of registration receipts. With a user-friendly interface, this system ensures a faster and more accurate registration process. This research has resulted in a system that can reduce the administrative burden on registration officers, minimize data input errors, and provide easier access for prospective students and parents/guardians. Evaluation results indicate that the system improves the efficiency of new student registration by 30% and has received positive feedback from users. It is expected that the implementation of this information system will make a positive contribution to the management of new student registration at the respective educational institution.